Kinetic Studies of Hydrodesulfurization of Vacuum Distillate - A.K.Mohammed, Abdul-Halim; A.K, Abdul-Monaem; A.A., Hiadar (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Vacuum gas oil (611-833)K was distilled from Kirkuk crude oil, which was obtained by blending the following fraction,light vacuum gas oil (611 - 650) K, medium vacuum gas oil (650-690)K, heavy vacuum gas oil (690-727)K and veryheavy vacuum gas oil (727-833)K.The vacuum gas oil was hydrotreated on a commercial cobalt-molybdenum alumina catalyst presulfied at specifiedcondition in a laboratory trickle bed reactor. The reaction temperature varied from (583-643)K over liquid hourly spacevelocity ranging between (1.5-3.75)h-1 , Hydrogen pressure was kept constant at 3.5 MPa with a hydrogen to oil ratioof about 250 L/LThe conversion results for desulfurization appeared to obey the second order kinetics. According to this model rateconstants for desulfurization reaction were calculated. Finally, the apparent activation energy (Ea), enthalpy ofactivation ( H*) and entropy (  S*) were calculated based on the values of rate constant (k). The calculated values ofEa, H* and  S* were 74.657 kJ/mole, 74.712 kJ/mole and 167.132 J/mole.k, respectively.